The drivers of Norway's house prices - Sila, Urban (OECD Publishing, 2020)
In this paper, we explore the drivers of house prices in Norway, using a cross-country panel framework. Empirical results confirm that house prices are determined by numerous demand and supply factors, including income, demographics, macroeconomic conditions, stock of housing and institutional features. The results suggest that high and rising house prices in Norway are principally driven by market fundamentals - high household incomes, wealth, low interest rates and a growing population. Yet, despite strong fundamentals, comparing predicted house prices as estimated by the model and observed house prices suggests that house prices in Norway have been overvalued to a degree since the global financial crisis. Some structural and regulatory features of the Norwegian housing market also put upward pressure on prices: the favourable tax treatment of home ownership, strict rent controls and lax tenant-landlord regulations. Improving further the responsiveness of housing supply to demand could also ease price pressures
Keywords: Education; Norway